PENGARUH KELOMPOK REFERENSI TERHADAP KEPUTUSAN PEMBELIAN KAWASAKI NINJA 250 CC: THE EFFECT OF REFERENCE GROUP ON PURCHASE DECISION OF KAWASAKI NINJA 250 CC - Sylvia Kartika WB; Rosyid Sidig (Konsentrasi Manajemen Pemasaran Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2018)
The purpose of this study is to examine the affect of reference groups on purchasing decision of Kawasaki Ninja 250 cc in the city of Jambi. Size of sample consist of 100 unit that chousen randomly. While data analysis used multiple regression analysis. The results showed that simultaneouly normative, value expression, and informative have significant role. But, based on partiall test normative has no significant affect. Hence, reference group has important rolel as marketing role. In this case, marekting tool should make good communication and relation to all the customer to make them parta of marketing tool. Keywords: normative influence, value expression, informative influence, and purchasing decisions